Socio-economic Relations between India and China: Understanding and Examining the Significance of Indian Culture - Nitasha Kaul,; DR. Rahul Varma,; Ms. Madhusmita Sing, (Al-Qanṭara, 2023)
China and India both have collectivistic civilizations, according to international studies on cultural exchange. It is unclear, nevertheless, whether and why, China and India's collectivism differs from one another. This study investigates if cultural legacy theories may account for why Chinese people value collectivism more than Indians. Online surveys were used to compile convenient samples (N China = 218, N India = 118), while 86 Americans made up the contrast group. In several approaches used here, the Chinese respondents outperformed the Indian respondents in terms of holistic thought, patriotism, nepotism, familism, and self-interdependence, while underperforming them in terms of assertiveness and argumentativeness. These results support the idea that Chinese people are more collectivistic than Indians, despite China and India being more collectivistic than the United States. The study went beyond an east-west comparison to deepen our understanding of individuality and collectivism. Keywords- India and China, Socio-economic